The impact of R&D innovation success on the relationship between R&D investment and financial leverage - Vincent O'Connell; Naser M. AbuGhazaleh; Yasean Tahat; Garvan Whelan (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This paper explores the interrelationship between R&D investment, financial leverage, and a firm's R&D innovation success. Using a sample of UK and EU firms, we predict that changes in one-year-ahead R&D investment are negatively associated with changes in financial leverage in the current period. Crucially, we also predict that this negative association is positively moderated by the extent to which firms are successful in generating commercially viable and technically feasible innovations from their R&D work. We use insights from International Accounting Standard (IAS) 38: Intangible Assets to measure R&D innovation success. Our empirical findings offer strong support for each of our theoretical predictions. Consequently, we contribute to the extant literature by demonstrating that R&D innovation success influences how firms finance their subsequent investments in R&D. Our work also shows that accounting disclosures have the potential to play an important role in open innovation networks.
Keywords: 650; capitalization of R&D; commercially viable; financial leverage; open innovation networks; R&D innovation success; R&D investment; R&D success; technically feasible